PERAN BRAND IMAGESEBAGAI PEMEDIASI PENGARUH COUNTRY OF ORIGINPADA BRAND EQUITY - Ni Luh Putu Mira, Pratiwi; Ni Nyoman, Kerti Yasa (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2015)
The aim of this study is to determine the mediating role of brand image on the influence of countryof origin on brand equity of Toyota car in Denpasar City. This research was conducted to 150 samples by implementing purposive sampling method. The data was collected by using instrument with 5 point Likert’s Scale. The data was analized with Structural Equation Modeling ( SEM ) technique. The results show that 1) country of origin has a positive effect on brand image, 2) country of origin is positively affect brand equi ty, 3) brand image is positively affect brand equity, and 4) brand image mediates the effect of country of origin on brand equity. It is recommended for Toyota Management to further highlight that Toyota is a made in Japan car with an image of developed countries. Additionally, Toyota  management can also improve  its brand image by making Toyota as the top brand award, so it will be able to increase the brand equity of the Toyota products.
Keywords: country of origin, brand image, brand equity